Current trends and future projection for addressing the burden of esophageal carcinoma in Asia: a comprehensive analysis (1990–2040) - Ma, Peng; Tan, Xiaohong; Hao, Tingting; Liu, Pengfei; Bai, Min; Dong, Lei (Frontiers in Oncology, 2025)
BackgroundEsophageal carcinoma (EC) significantly impacts global health, particularly in Asia, where many low- and middle-income countries face substantial burdens despite advancements in some regions.ObjectiveThis study analyzed EC’s spatial and temporal distribution in Asia using the Global Burden of Disease (GBD) database, aiming to forecast future burdens and support effective prevention strategies.MethodsData from 48 Asian countries (1990-2021) were extracted from the GBD database, covering incidence, prevalence, deaths, disability-adjusted life years (DALYs), risk factors, and socio-demographic index (SDI). R and GraphPad Prism were used to assess changes and predict future trends.ResultsFrom 1990 to 2021, EC’s disease burden in Asia generally declined, with significant regional and sex disparities. East Asia showed the most improvement despite having the highest burden. Conversely, South and Southeast Asia experienced limited progress, with some areas seeing increased burdens. Males consistently had higher burdens than females, especially in East Asia. Future projections (from 2022 to 2040) suggested a slight rise in incidence in East Asia, while improvements in South and Southeast Asia may remain limited, though an overall burden decline was expected.ConclusionThe reduction in Asia’s EC burden underscored the impact of medical advances and public health efforts, but regional and sex disparities persist. Future strategies should enhance health resources in under-resourced and high-risk areas and implement targeted policies to address health inequalities and promote balanced public health development across Asia.